Evaluating the Suitability of Online Courses using the ELECTRE Method - S Sahyunu; Jimmy Moedjahedy; Iwan Adhicandra; Yogasetya Suhanda; Usanto S; Robbi Rahim (STAI Hubbulwathan Duri, 2023)
This study aims to explore the use of the Elimination and Choice Expressing Reality (ELECTRE) method for selecting and evaluating online courses. The pairwise comparison method determined a set of criteria and weights, including course quality, instructor experience, accreditation, student engagement, flexibility, technical support, and cost. The study used a mixed-methods approach, which means it combines quantitative and qualitative data. The ELECTRE method was then applied to rank five online courses based on their suitability for the participants' needs and expectations. The concordance and discordance indices were calculated for each course, and the net flow was used to determine the ranking. The results showed that the ELECTRE method can be a useful tool for participants in choosing and evaluating online courses based on a set of tailored criteria and weights. Future research could investigate how the results of the ELECTRE method can be combined with other methods to enhance the accuracy and validity of the ranking. Overall, the ELECTRE method provides a useful framework for participants to decide which online course is best suited to their individual preferences and goals.